1995
DOI: 10.1002/ajim.4700280307
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among workers at a plastics manufacturing and research and development facility: 1946–1988

Abstract: Mortality through 1988 was studied for 5,932 male employees who worked between January 1, 1946 and December 31, 1967 at a New Jersey plastics manufacturing and research and development facility. The cohort was followed for an average of 32 years and included 1,859 deaths. Potential exposures included asbestos, formaldehyde, and polyvinyl chloride (PVC). Mortality rates for the cohort were compared to both U.S. and state mortality rates, and analyses were also performed by lagging duration of employment. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…For some subjects, occupational history was provided by a proxy, which could have resulted in misclassification of formaldehyde exposure. However, these errors significant (6,9), one among women only (13). In two smaller cohorts of health professionals, statistically significant inverse associations (standardized mortality ratios) were reported (8,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For some subjects, occupational history was provided by a proxy, which could have resulted in misclassification of formaldehyde exposure. However, these errors significant (6,9), one among women only (13). In two smaller cohorts of health professionals, statistically significant inverse associations (standardized mortality ratios) were reported (8,16).…”
Section: Discussionmentioning
confidence: 99%
“…Both were among the case-control investigations with the largest numbers of exposed cases. Among the same 23 studies, only a few further analyzed each of the more refined measures of formaldehyde exposure, including exposure level (2,10,12,27), lifetime cumulative exposure (2,6,23,28), duration of exposure (2,6,7,9,10,18,24), time since first exposure (6,7,18), and peak exposure (2). However, even when formaldehyde exposure was analyzed using these more detailed metrics, increased risks were observed only in two studies with high exposure level (10) and longer exposure duration (24), and a decreased risk was reported with longer duration in another (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although three case-control studies observed a 2-to 4-fold excess risk of NPC (177,199,203), and a U.S. study found an increased risk of type I but not type II or III NPC (204), most case-control studies in high-and low-incidence areas (40,179,199,200,205,206), as well as occupational cohort studies in nonendemic areas (207)(208)(209)(210)(211)(212)(213), found no significant association of formaldehyde exposure with overall NPC risk. Cohorts of formaldehyde workers in Denmark (214) and fiberboard manufacturers in Sweden (215) experienced a significant excess of nasal cavity cancers or NPC, respectively, but U.S. cohorts of male embalmers and funeral directors, who also have occupational formaldehyde exposure, had no excess risk (216,217).…”
Section: Risk Factorsmentioning
confidence: 99%
“…This pattern was more pronounced for benign intracranial tumors than for brain cancer, suggesting better detection as the explanation, and was more pronounced for men than for women. In contrast, many studies of the petroleum and petrochemical industries found that white collar workers had brain cancer mortality rates close to, or slightly below, the general population rates [Hoar and Pell, 1981;Waxweiler et al, 1983;Chiazze et al, 1986;Bond et al, 1987;O'Berg et al, 1987;Teta et al, 1990;Arnetz et al, 1991;Teta et al, 1991;Delzell et al, 1992;Dell and Teta, 1995;Satin et al, 1996]. On balance, the generally high economic status of the subjects is unlikely to explain entirely the excess of brain cancer in B500.…”
Section: Brain Cancermentioning
confidence: 75%